PENGARUH PARAMETER PEMESINAN BUBUT TERHADAP KEKASARAN PERMUKAAN PADA BAJA AISI 4340 - Adha Mahendra, Erlian; Hermawan, Yuni; Triono, Agus; Rozy Hentihu, M. Fahrur; Sakura, Rahma Rei (Jurusan Teknik Mesin, 2025)
This research evaluates the influence of lathe machining parameters, such as spindle speed,cutting speed, and feed depth, on the surface roughness (Ra) on the wheel axle of an electric car madefrom AISI 4340 steel. Measurements were carried out using a TR220 surface roughness tester machine,which recorded the highest roughness of 10.107 μm and the lowest was 4.041 μm. The results showedthat feed speed contributed 51.24%, spindle speed 35.82%, and cutting depth 12.94% to surfaceroughness.The optimal combination of machining parameters to produce a surface with low roughness is aspindle speed of 770 m/min, a cutting depth of 0.5 mm, and a feed speed of 120 mm/s. Small infeed depths are ideal for producing smooth surfaces, but compromises may be necessary for production efficiency. In addition, high cutting speeds provide optimal results if heat and tool wear can be controlled. Optimizing these parameters is critical to improving product quality, performance and lifetime.Keywords: Surface Roughness, AISI 4340 Steel, Lathe Machining